The Variable Determinacy Thesis - Surden, Harry (Science and Technology Law Review, 2011)
This Article proposes a novel technique for characterizing the relative determinacy of legal decision-making. I begin with the observation that the determinacy of legal outcomes varies from context to context within the law. To augment this intuition, I develop a theoretical model of determinate legal decision-making. This model aims to capture the essential features that are typically associated with the concept of legal determinacy. I then argue that we can use such an idealized model as a standard for expressing the relative determinacy or indeterminacy of decision-making in actual, observed legal contexts. From a legal theory standpoint, this approach – separating determinacy and indeterminacy into their constituent conceptual elements – helps us to more rigorously define these theoretical ideas. Ultimately, from a practical standpoint, I assert that this framework assists in understanding why legal outcomes in certain contexts are determinate enough to be amenable to resolution by computers.